The Case Study on the Relationship Between Crude Oil Prices Stimulating the Economic Growth in Malaysia - Yeoh Wee Win (MultiTech Publisher, 2021)
The uncertainty in the crude oil prices had always become the limelight attracting attention of many individuals and businesses over time concerning on the economic condition for the country. This concerns had not become any exception for Malaysia as the developing nation where the constant rising of the crude oil prices had been viewed as the contributor towards the development of the local economic growth in the country. With this, the problem statement had been identified to study the relevance impact and relationship between the drive of the crude oil price against the growth of the real GDP (Gross Domestics Product) rate in Malaysia. The quantitative study had bene designed to study the data based on the timeline from 2008 o 2023 to cover the economic cycle from the last financial crisis to recent time. The outcome of the study had provided clear evidence to reject the initial suggestion as there is not sufficient evidence to present the significant relationship between the crude oil price against the real GDP growth for the country. Therefore, the study had concluded with the irrelevance impact from the price of crude oil in affecting the economic growth in Malaysia where the future scope of study had been recommended to explore the similar study in other country as well as replacing other economic variables to understand further on the impact from crude oil prices in the economy